2002
DOI: 10.1002/jbt.10018
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a stress‐induced gene by insecticides in the midge, Chironomus yoshimatsui

Abstract: Stress proteins (heat shock proteins, HSPs) have been proposed as general biomarkers for environmental monitoring. In the present study, we evaluated the environmental stress-burden on the aquatic midge Chironomus yoshimatsui using hsp70 expression. Larvae collected from streams receiving polluted runoff (field strain) were resistant to the organophosphorus insecticide, fenitrothion (F), and the synthetic pyrethroid, ethofenprox (E), whereas a strain originally collected from an unpolluted area (susceptible st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…For example, up-regulated expression of hsp70 under heat stress was found in many insects, such as noctuid pest moth species Helicoverpa zea (Boddie) (Zhang & Denlinger, 2010), Spodoptera exigua (Hübner) (Xu et al, 2011) and S. litura (Fabricius) (Shen et al, 2014), hymenopterous wasp parasitoids, Macrocentrus cingulum (Xu et al, 2010) and Cotesia vestalis Haliday (Braconidae) (Shi et al, 2013) and the fruit fly, D. melanogaster (Udaka et al, 2010). Increased expression of hsp70 was observed when the non-biting midge, Chironomus yoshimatsui Martin & Sublette (Diptera: Chironomidae), or D. melanogaster was treated with pyrethroid insecticide (Mukhopadhyay et al, 2002;Yoshimi et al, 2002). The insect hsp70 expression was strongly up-regulated in response to heavy metals, including Zn, Cu, Cd, Ag, Pb and Ni (Sonoda et al, 2007;Augustyniak et al, 2009;Karouna-Renier & Rao, 2009;Ahamed et al, 2010).…”
Section: Source Of Insectmentioning
confidence: 99%
“…For example, up-regulated expression of hsp70 under heat stress was found in many insects, such as noctuid pest moth species Helicoverpa zea (Boddie) (Zhang & Denlinger, 2010), Spodoptera exigua (Hübner) (Xu et al, 2011) and S. litura (Fabricius) (Shen et al, 2014), hymenopterous wasp parasitoids, Macrocentrus cingulum (Xu et al, 2010) and Cotesia vestalis Haliday (Braconidae) (Shi et al, 2013) and the fruit fly, D. melanogaster (Udaka et al, 2010). Increased expression of hsp70 was observed when the non-biting midge, Chironomus yoshimatsui Martin & Sublette (Diptera: Chironomidae), or D. melanogaster was treated with pyrethroid insecticide (Mukhopadhyay et al, 2002;Yoshimi et al, 2002). The insect hsp70 expression was strongly up-regulated in response to heavy metals, including Zn, Cu, Cd, Ag, Pb and Ni (Sonoda et al, 2007;Augustyniak et al, 2009;Karouna-Renier & Rao, 2009;Ahamed et al, 2010).…”
Section: Source Of Insectmentioning
confidence: 99%
“…In recent years, some genes have been described as biomarkers for toxicant exposures including, among others, those for heat shock proteins (Hsp70, Hsc70, Hsp90, Hsp40), ribosomal proteins, cytochrome P450, and nuclear receptors Gopalakrishnan et al, 2011;Morales et al 2011;Planelló et al 2007;2008;Park and Kwak 2008Martínez-Paz et al 2012;Ozáez et al 2013). Hsp70 has been sequenced and evaluated as a biomarker of exposure to metals and insecticides in other species of chironomids, such as Chironomus yoshimatsui and Chironomus dilutus (Yoshimi et al 2002;Karouna-Renier and Rao 2009). However, there is still scarce DNA sequence information for these aquatic species and, in particular, the family of small Hsps genes has not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the expression of hsp70 is induced in response to 0.4 mg/l fenitrothion (organophosphate) and 0.4 mg/l ethofenprox (pyrethroid) in the midge, C. yoshimatsui (Yoshimi et al, 2002). Mukhopadhyay et al (2002) showed the induction of hsp70 expression in response to cypermethrin (pyrethroid) at 0.002 ppm using transgenic D. melanogaster.…”
Section: Discussionmentioning
confidence: 99%
“…In one such study, Yoshimi et al (2002) reported that the expression of hsp70 in the midge, Chironomus yoshimatsui, is induced in response to organophosphate (fenitrothion) and pyrethroid (ethofenprox). They suggested that hsp70 is a sensitive indicator of low-level exposure to certain insecticides.…”
Section: Introductionmentioning
confidence: 99%